Editorial - Mileo Taher, Dhyogo (Revista de Engenharia Térmica, 2024)
It is with immense sadness and huge disbelief that we received the news of the passing of Dr Wellington Balmant, in July 2023. Dr. Balmant had an incredible love and passion for science and left the scientific and academic world too soon. I had the privilege of meeting Dr. Balmant when I started my academic career, in 2010. I was immensely fortunate for having him as my first supervisor. With a rare sense of humor, he conducted complex challenges assigned to him very seriously, but with incomparable lightness and grace. In total, 14 years of personal and scientific development alongside Dr. Balmant, who led his research, teammates, and students brilliantly. Thanks to the hours spent working together, I was able to develop a strong friendship and had the opportunity to learn about his benevolent and generous persona. Considered by me as a brother, Dr. Balmant gave me the privilege of being invited to work with him on other projects that he was the leader. I learned a lot, from the most technical and scientific topics to personal and everyday situations. It is not an exaggeration to say that a large part of the person and scientist I became, as well as a large part of my academic achievements, was due to Dr. Balmant. And I'm sure there are many others who find themselves in the same situation. And that is why I speak on behalf of myself and those who had the privilege of meeting this great human being, scientist, researcher, teacher, and father. thank you! RETERM expresses its gratitude and wishes his family to overcome this difficult time with great faith and strength of spirit.